Comparison of Transperineal Mapping Biopsy Results with Whole-Mount Radical Prostatectomy Pathology in Patients with Localized Prostate Cancer - Darren J. Katz; Rodrigo Pinochet; Kyle A. Richards; Guilherme Godoy; Kazuma Udo; Lucas Nogueira; Angel M. Cronin; Samson W. Fine; Peter T. Scardino; Jonathon A. Coleman (Prostate Cancer)
Objective. We sought to evaluate the accuracy of transperineal mapping biopsy (TMB) by comparing it to the pathology specimen of patients who underwent radical prostatectomy (RP) for localized prostate cancer. Methods. From March 2007 to September 2009, 78 men at a single center underwent TMB; 17 of 78 subsequently underwent RP. TMB cores were grouped into four quadrants and matched to data from RP whole-mount slides. Gleason score, tumor location and volume, cross-sectional area, and maximal diameter were measured; sensitivity and specificity were assessed. Results. For the 17 patients who underwent RP, TMB revealed 12 (71%) had biopsy Gleason grades ≥ 3 + 4 and 13 (76%) had bilateral disease. RP specimens showed 14 (82%) had Gleason scores ≥ 3 + 4 and 13 (76%) had bilateral disease. Sensitivity and specificity of TMB for prostate cancer detection were 86% (95% confidence interval [CI] 72%–94%) and 83% (95% CI 62%–95%), respectively. Four quadrants negative for cancer on TMB were positive on prostatectomy, and six positive on TMB were negative on prostatectomy. Conclusion. TMB is a highly invasive procedure that can accurately detect and localize prostate cancer. These findings help establish baseline performance characteristics for TMB and its utility for organ-sparing strategies.